2002
DOI: 10.1017/s0950268802007811
|View full text |Cite
|
Sign up to set email alerts
|

Rubella antibody loss rates in Korean children

Abstract: We followed students in eight elementary schools for rubella antibody from 1993 to 1996 (602 pairs) and 1996-9 (588 pairs) in Gyeonggi Province, Korea. We tested rubella IgG and administered rubella vaccine to the children with the titres < 10 IU/ml. The loss rates of rubella IgG during the follow-up periods were 14.3 and 15.8%, respectively. Among vaccinated groups, the loss rate was 18.8%, which was significantly higher than 13.8% of the mixture of natural and vaccine-induced immunity groups. The group that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Susceptibility rates were different by gender, which can be attributed to the immunologic effect. In our study, rubella immune loss rate during 3 yr was observed more frequently among boys (24). In the rubella epidemic of Korea in 1996, among 5 to 14 yr old, the incidence rate of boys (55/100,000) was higher than that of girls (19/100,000).…”
Section: Discussionsupporting
confidence: 41%
“…Susceptibility rates were different by gender, which can be attributed to the immunologic effect. In our study, rubella immune loss rate during 3 yr was observed more frequently among boys (24). In the rubella epidemic of Korea in 1996, among 5 to 14 yr old, the incidence rate of boys (55/100,000) was higher than that of girls (19/100,000).…”
Section: Discussionsupporting
confidence: 41%
“…The seroprevalence of rubella in Korean populations was assessed previously in infants, children and adolescents 12–16. One study on 5393 students from eight elementary schools in the Gyeonggi province, Korea in 1993, 1996 and 1996 had reported that the age-adjusted rubella susceptibility rate was 22.9% 14.…”
Section: Discussionmentioning
confidence: 99%
“…One study on 5393 students from eight elementary schools in the Gyeonggi province, Korea in 1993, 1996 and 1996 had reported that the age-adjusted rubella susceptibility rate was 22.9% 14. Another study performed during the same study period had reported that rubella antibody loss rates were 14.3%–15.8% in Korean children 12. In a 2005 population-based survey in Nonsan, Korea, age-appropriate immunisation among urban-rural children aged 24–35 months had reported that the age-appropriate MMR immunisation rate was 61.1%–97.4% 16.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have consistently found antibody response dynamics and patterns following rubella vaccination that depended on rubella-specific pre-immunization titer and the propensity of the individual to respond to vaccination [7,15,16,38]. The same holds true for the measles component of the MMR vaccine, where seronegativity and low antibody titer following previous vaccination were demonstrated to be a significant risk factor for persistent low antibody titer and/or seronegativity after a subsequent dose of MMR [39][40][41][42].…”
Section: Discussionmentioning
confidence: 53%